Intramuscular Diphenhydramine Does Not Affect Acute Doxorubicin Infusion-Related Arrhythmia Number or Severity in a Prospective Crossover Study in Canine Lymphoma: A Pilot Study - Willcox, Jennifer Lindley; Belanger, Catherine; Burton, Jenna Hart; Yu, Lydia; Ueda, Yu; Visser, Lance C.; Skorupski, Katherine; Stern, Joshua A. (Frontiers in Veterinary Science, 2020)
Background: Doxorubicin (DOX) is one of the most effective chemotherapeutics for canine high-grade lymphoma. In addition to dose-dependent chronic cardiotoxicity, DOX can trigger acute cardiac arrhythmias during drug infusion. Diphenhydramine premedication is commonly used, as histamine release is a proposed mechanism for DOX-associated arrhythmogenesis. Hypothesis/Objectives: The study objectives were to evaluate the incidence and severity of DOX infusion-related cardiac arrhythmias in dogs with high-grade lymphoma and evaluate the effect of diphenhydramine premedication on arrhythmia frequency and severity during and after DOX infusion. Animals: Twenty-two client-owned dogs with cytologically/histopathologically confirmed high-grade lymphoma were recruited, of which 19 were enrolled and 9 completed the study. Methods: Dogs were screened by echocardiogram and concurrent electrocardiogram for this randomized prospective crossover study. Group A received no premedication for DOX #1 and was premedicated with diphenhydramine for DOX #2; Group B received diphenhydramine with DOX #1 and no premedication for DOX #2. For both visits, Holter monitor data were collected for 1 h pre-DOX and 3 h post-DOX administration. Results: Nineteen dogs were enrolled and 9 dogs [Group A (5), Group B (4)] completed the protocol. There was no statistical difference between the DOX alone and DOX + diphenhydramine when evaluating the total number of ventricular premature complexes (VPCs, P = 0.34), change in VPCs/hour (P = 0.25), total number of atrial premature complexes (APCs, P = 0.5), change in APCs/hour (P = 0.06), or ventricular arrhythmia severity score (P > 0.99). Conclusions and clinical importance: This study demonstrates that in these dogs with rigorous pretreatment cardiovascular screening, DOX infusion did not induce significant arrhythmias. Furthermore, these data suggest that, with this screening approach, diphenhydramine may not alter the arrhythmia number or severity in canine DOX recipients.